Supporting Immigrant Families and Rural Schools: The Boundary-Spanning Possibilities of an Adult ESL Program. (October 2019) - Shiffman, Catherine Dunn
Purpose: There has been a significant increase in the number of immigrant families moving to rural communities across the United States. Yet limited research exists that explores relationships between immigrant families and schools in these communities. Rural school districts are often challenged by insufficient resources, expertise, and infrastructure to respond. Adult English as a second language (ESL) programs can be valuable partners. This article explores how instructors in a regional adult ESL program supported relationships between immigrant families and schools in a rural Virginia school district.Research Methods: A case study was conducted between 2014 and 2015. Data collection included observations of adult ESL classes; semistructured interviews with adult ESL instructors, parents of school-age children, and school district leaders and teachers; open-ended questions on a parent survey; and documents.Findings: Four interrelated practices of the adult ESL instructors facilitated understanding and communication between immigrant families and K-12 educators. Adult ESL instructors disseminated information, explained cultural norms and expectations, coached family-school interactions, and created opportunities to connect families and educators. Supporting conditions included characteristics of the adult ESL classes, district leadership and sense of urgency, and multilayered relationships of professionals and actions of the adult ESL coordinator.Implications for Practice: Given the right conditions, adult ESL programs can be valuable partners for rural education leaders seeking to strengthen engagement with immigrant families. These programs can facilitate linkages between schools and adult ESL learners who are parents or caregivers and can be a professional development resource for building district capacity to engage with immigrant families.